Climate change education in rural Colorado schools - Scheer, Madison, author; Balgopal, Meena, advisor; Denning, Scott, committee member; Enns, Kellie, committee member (Colorado State University. Libraries, 2021)
Earth system science education is becoming more timely as our understanding of climate change (CC) and the effects across our social ecology systems increase. Climate literacy, however, is threatened by hyper-political discourse regarding the anthropogenic causes of climate change, which is especially heightened in rural spaces, where residents' livelihoods are often the target of scrutiny by media and scientists. In this study, rural Colorado teachers' (n=9) explanations and perceptions of their climate change education (CCE) instructional choices were examined using instrumental case study methodology. This study was written with the intention for submission to the Journal of Environmental Education or Research in Science Education. Analysis of multiple data sources (interviews, observations, curricular artifacts, student assessments, school websites) resulted in the identification of three cases defined by the teachers' acceptance of anthropogenic causes of climate change, their use of Claim, Evidence, and Reasoning (CER) instructional model, and their sense of belonging. Participants were grouped into one of three cases: (1) Accepts and teaches CC using CER, (2) Accepts CC but does not use CER, and (3) Does not accept nor teach CC. Teachers' competence and confidence with climate science (knowing) as well as their sense of belonging in their rural school and community (belonging) affected how they framed (Scientific uncertainty or Conflict/Strategy) climate change to their students. By learning how rural science teachers communicate CC in their classrooms, science education experts and climate scientists can collaborate to (1) design meaningful and effective professional development workshops and (2) collate curricular resources, including empirical evidence for CC, so rural science teachers feel prepared to teach CC as a socioscientific issue. Moreover, with access to empirical evidence, rural science teachers are better positioned to model scientific argumentation using the CER model in their lessons. Research focused on climate literacy is fundamental to creating an informed generation capable of making conservation, land stewardship, and natural resource management decisions. Rural teachers and students must be included in endeavors to increase climate literacy.
Keywords: environmental education; science; teacher; rural; climate change; socioscientific issue